PENGETAHUAN, SIKAP DAN TINDAKAN MASYARAKAT TERHADAP PENCEGAHAN COVID-19 DI DESA SITOMPUL KECAMATAN SIATAS BARITA KABUPATEN TAPANULI UTARA TAHUN 2021 - Marni Siregar; Emilia Silvana Sitompul; Juana Linda Simbolon (Jurnal Maternitas Kebidanan, 2022)
The COVID-19 pandemic that has hit the world is a phenomenon that was never expected in modern civilization. The pandemic conditions have not yet shown that it will end, demanding that everyone be disciplined in implementing preventive measures with the 5M health protocol (wearing masks, maintaining distance, washing hands, staying away from crowds, reducing mobility). However, not everyone obeys these rules. People's perceptions are sometimes wrong, many do not understand the dangers of transmitting COVID-19. This study aims to determine the knowledge, attitudes and actions of the community towards the prevention of Covid-19 in Sitompul Village during the pandemic. The design of this research is descriptive. Results The level of community knowledge about COVID-19 prevention in Sitompul Village is good. The attitude of the community towards the prevention of COVID-19 in Sitompul Village is good. Community action against COVID-19 prevention in Sitompul Village is good